INCREASING AMENDMENT OF TEACHING PROCEDURES IN EDUCATIONAL SYSTEM - Xidirova Nilufar Abdiaxatovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This study looks at different teaching methods in various subjects and shows  why  they  are  important  for  people  working  in  education.  Learning  good knowledge in a certain subject is an important goal in teaching. In different situations, teachers need to choose the right methods to get good results in learning activities. The results  of  this  study  can  be  used  in  many  schools  and  educational  institutions.  It explains the main parts of lesson planning, how teaching works, and what happens in the classroom.